All you need to know about action research - McNiff, Jean.; Whitehead, Jack. (Los Angeles : SAGE, 2011)
The authors provide an easy-to-follow introduction to action research that presents a guide to the history and philosophy that underpin action research, coverage of the main theoretical debates in action research, and help to anyone undertaking their own action research project.
Includes bibliographical references and index.
Keywords: Action research